سورة الواقعة دراسة بيانية - شرقي, فاطمة; كير, هنية (جامعة الوادي university of eloued, 2019)
الحمد لله رب العالمين والصلاة والسلام على أشرف المسلمين أما بعد: تتناول هذه المذكرة د ا رسة سورة الواقعة د ا رسة بيانية وذلك للكشف عن خصوصية النص القرآني وبلاغته وفصاحة ألفاضه وسر وضعها دون م ا ردفتها والتعرف على أبعاده الجمالية ودقة معانيه وبلاغة ت ا ركيبه حيث وقفنا من خلال هذا البحث على كل آية اتضح لنا فيها وجها بلاغيا أو لمسة بيانية أو لفضة كان لها سر في وضعها دون م ا ردفاتها وتبين لنا من خلال هذه الد ا رسة أن القرآن معجز في تركيبه ومعانيه وذلك لما حوته السورة من أوجه بلاغية ولمسات بيانية فالقرآن صالح لكل زمان وقابل للبحث والنظر في كل رؤية جديدة تتجلى معلومات وأفاق جديدة . This note deals with the stady of surat al-waqia In order to reveat the privaccy of the Koran and this rhetoric and calarity o word . and the secret of their status withous sunonym And to identify the aesthetic dimension and accuracy of its meaning and eloquence structures,wher we stood through this research on each verse turned out to us in wich the face of a retorical or graphic thouh or a word that had a .secret in the development without sunonum Through this stady ,we find that the Quran is miraculous in its composition and its meaning because its characterized by rhetorical and graphic touches The Quran valid for all time and it is possible to search and look at every new in formation and horizons .
لغة